Entre o sério e o cômico na fantasia distópica: uma análise das representações de herói, corpo e sociedade em Temporada dos Ossos - Silva, Rafael Oliveira da (2021)
Fantasy and dystopia seem to have fallen in the likes of young readers through books like Harry Potter (1997) and Hunger Games (2008). These books present an alternative way of representing reality, subvert the official worldview of life and present us with a carnivalized reality, whether through magic or a dystopian future. While fantasy brings laughter, dystopia brings fear. In Bone Season (2016) we are introduced to a world in which clairvoyance is real and some humans have powers, however, all types of clairvoyance are forbidden and the government uses control of freedom to maintain it. We are, therefore, facing what we call in this research of dystopian fantasy, a hybrid genre that merges traces of fantasy and dystopia, thus building what appears to be a hypermodern example of a serious-comic novel. The problem of dystopian fantasy stems from the clash between laughter – that erodes the seriousness of the world by subverting it in different ways, through fantasy – and the fear – that, on the contrary, seeks to solidify it through the violent maintenance of power, in dystopia. Furthermore, we recognize that the representations of hero, body and society of dystopian fantasy differ from those commonly found in fantasy and dystopia. To anchor this positioning, the present work proposes, based on the postulates of the Bakhtin Circle, about issues of discursive genre, hybrid discursive genre and carnivalization, a dialogical analysis of dystopian fantasy as a genre that converts fantasy and dystopia in hypermodernity, as serious-comical genre, from the book Temporada dos Ossos (2016), by the british author Samantha Shannon. The research is inserted in the mixed, hybrid and undisciplinary area of applied linguistics and is also anchored in a theoretical framework of philosophy, literary and cultural studies based on the works of Han, Hall, Canclini, Bauman and Matangrano. Methodologically, it develops from a qualitativeinterpretative perspective and uses the indicative paradigm, proposed by the historian Carlo Ginzburg, to obtain the data. The results point out representations of hero, body and society that insert into the heterodiscourse of the dystopian fantasy novel elements that are unusual to the fantastic youth literature. Such representations have a carnivalized content that dramatically alters their relationship with the audience and the social orientation of the youth fantasy novel.